2017
DOI: 10.1073/pnas.1702973114
|View full text |Cite
|
Sign up to set email alerts
|

Local destabilization, rigid body, and fuzzy docking facilitate the phosphorylation of the transcription factor Ets-1 by the mitogen-activated protein kinase ERK2

Abstract: Mitogen-activated protein (MAP) kinase substrates are believed to require consensus docking motifs (D-site, F-site) to engage and facilitate efficient site-specific phosphorylation at specific serine/ threonine-proline sequences by their cognate kinases. In contrast to other MAP kinase substrates, the transcription factor Ets-1 has no canonical docking motifs, yet it is efficiently phosphorylated by the MAP kinase ERK2 at a consensus threonine site (T38). Using NMR methodology, we demonstrate that this phospho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 22 publications
(26 citation statements)
references
References 51 publications
0
26
0
Order By: Relevance
“…In addition to the important role played by DUSPs in regulating overall ERK activity, activated ERK1/2 catalyzes the phosphorylation of numerous nuclear transcription factors, exemplified by ETS; ELK-1, a member of the ETS oncogene superfamily) [46,47]; c-Fos, a component of the activator protein-1 (AP-1) complex [48]; and Forkhead Box O (FOXO) [49], all of which arise through both active and passive nuclear translocation of phosphorylated ERK1/2 [1,50]. Of note, constitutively activated RAS-RAF-MEK-ERK was found to be present in about 30% of all human cancer tissues [51].…”
Section: An Overview Of Erk Signaling Componentsmentioning
confidence: 99%
“…In addition to the important role played by DUSPs in regulating overall ERK activity, activated ERK1/2 catalyzes the phosphorylation of numerous nuclear transcription factors, exemplified by ETS; ELK-1, a member of the ETS oncogene superfamily) [46,47]; c-Fos, a component of the activator protein-1 (AP-1) complex [48]; and Forkhead Box O (FOXO) [49], all of which arise through both active and passive nuclear translocation of phosphorylated ERK1/2 [1,50]. Of note, constitutively activated RAS-RAF-MEK-ERK was found to be present in about 30% of all human cancer tissues [51].…”
Section: An Overview Of Erk Signaling Componentsmentioning
confidence: 99%
“…One docking motif, named "DEF" (aka FRS), binds a pocket near the activation segment of ERK1/2 and typically contains the consensus hydrophobic sequence Phe/Tyr-Xxx-Phe/Tyr located 6-20 residues C-terminal to the phosphorylation site (42,43). A second motif, named "DEJL" (aka Ddomain or DRS), binds a pocket distal to the catalytic cleft in ERK1/2, and often contains the consensus sequence (Arg/Lys)2-3-(Xxx)2-6-ΦA-Xxx-ΦB, where ΦA and ΦB are hydrophobic residues (44). DEJL motifs are more commonly observed, but can be harder to identify because they do not share exact consensus sequences and can vary in their distances from the phosphorylation site (43,45,46).…”
Section: Combined Analyses Of Four Inhibitors Of Mkk1/2 or Erk1/2mentioning
confidence: 99%
“…Several years ago, the 1,2,4-triazol-3-one, BI-78D3 was identified as a weak inhibitor of the interaction between the scaffold protein c-Jun N-terminal kinase inhibitory protein 1 (JIP1) and the c-Jun N-terminal kinase 1, JNK1 37 . We found that BI-78D3 impedes the ability of a constitutively active form of the ERK kinase, MKK1 (MKK1G7B) 38 to phosphorylate ERK1 and ERK2 in vitro and also impedes the ability of activated ERK1 and ERK2 to phosphorylate v-ets erythroblastosis virus E26 oncogene homolog 1 (Ets-1; a construct including the residues 1–138 that is necessary and sufficient for ERK-mediated phosphorylation, was used 39 ) (Fig. 1b).…”
Section: Resultsmentioning
confidence: 99%